Pergeseran Budaya Dari Rokok Konvensional Ke Rokok Elektrik Pada Customer Counter Vapor Kito Di Kota Palembang - Rizqullah, Muhammad Naufal; Maharani, Dwi (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2023)
Abstract The development towards something more modern will definitely occur in human life which includes various aspects such as technology, knowledge, lifestyle, culture, and others. The problem of smoking is an issue that is still pro and contra in society. Therefore, many people choose to use certain methods during the transition period until they can be free from conventional cigarettes. The main purpose of the creation of electric cigarettes is to help smokers quit the habit of using conventional cigarettes. The formulation of the problem in this study is "How is the cultural shift from conventional cigarettes to electric cigarettes at Counter Vapor Kito customer in Palembang City?". The purpose of this study was to determine the cultural shift from conventional cigarettes to electric cigarettes at Counter Vapor Kito customers in Palembang City. This study uses a descriptive method, using interview data collection techniques, observation, documentation and data analysis with qualitative techniques. Keywords: Communication, Conventional Cigarettes, Culture, Electric Cigarettes